Sistem Informasi Penyuluhan Pertanian di Dinas Pertanian dan Ketahanan Pangan Kabupaten Padang Pariaman - Surya Daren Hafizh; Fajar Pradana; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Department of Agriculture and Food Security of the District of Padang Pariaman is an element of the government that focuses on implementing agricultural matters whose responsibilities encompasses increasing the quality of agriculture in Padang Pariaman. Hence, training activities were planned encompasses increasing the quality of agriculture. The training activities involve field counselor, the chairman of BPP, department staff and head of the department. Before the activity is carried out, a program draft must be formed containing the plan and the design of the activities for next year. For every activity, the field counselors have an obligation to submit the field report containing the results of the activity and the usage of available funds. The process of creating the program draft and report starting from planning and approval of the documents requiring a huge amount of time. To make the steps more efficient, a solution is proposed which is in the form of creating an information system for agricultural training events using an SDLC waterfall method. During the analysis and designing phase, a model is built to ease the communication between developers and developers in hopes of finding the best solution. The models built in the analysis and designing phase are the use case diagram, use case scenario, sequence diagram, and class diagram. The system that was built will then be tested using the whitebox testing and blackbox testing. The results from the testing showed was near 100% valid which described the system has worked well and can help improve agricultural training activities in the district.